Identificación de espacios físicos utilizando realidad aumentada geolocalizada: caso de estudio UAN sede Sur (2024)
The present study focused on the identification of physical spaces at Antonio Nariño University using geolocated augmented reality using Unity and Vuforia Image Targets. The main objective of the project was to develop an application that would allow students and visitors to the university to identify the different physical spaces accurately and efficiently on campus. To achieve this objective, an analysis of user requirements and needs was carried out, the necessary elements were defined, programming and graphic design were carried out, and field tests were carried out to evaluate the functionality and usability of the application.